H.263 Based Video Codec for Real-Time Visual Communications Over Wireless Radio Networks - Bahl, Victor; Chlamtac, Imrich (Institute of Electrical and Electronics Engineers, Inc., 1997)
With the emergence of the International Telecommunication Union's (ITU) H.263 video coding standard, real-time visual communications over low-bandwidth, low-error-rate wired telephone networks is now possible. Unfortunately, because of the nature of the algorithms employed within this compression standard and due to the inherent limitations of the radio environment, the H.263 coded video performs pearly when employed over bandwidth-limited, error-prone wireless channels. In this paper we propose an intuitive, low-complexity, pre-compression scheme that improves the performance of H.263 coded video over radio channels. In our scheme video frames are spacially segmented into regions of different perceptual importance before being compressed independently with the H.263 encoder. This allows us to apply unequal error protection and prioritized transmission to achieve at least a minimum temporal resolution at the receiver. Additionally, with this technique, both spatial and temporal error propagation is limited and through intra-frame statistical multiplexing transmission bandwidth is utilized optimally. The results demonstrate that in the presence of severe error conditions and severe bandwidth constraints, our modified H.263 video codec exhibits better error concealment, better temporal resolution, and better bandwidth utilization properties than the original H.263 video codec.